Poetics and Politics Net Structures and Agencies in Early Modern Drama - Bernhart, Toni; Drnovšek, Jaša; Kilian, Sven Thorsten; Küpper, Joachim; Mosch, Jan (De Gruyter, 2018)
Far from teleological historiography, the pan-European perspective on Early Modern drama offered in this volume provides answers to why, how, where and when the given phenomena of theatre appear in history. Using theories of circulation and other concepts of exchange, transfer and movement, the authors analyze the development and differentiation of European secular and religious drama, within the disciplinary framework of comparative literature and the history of literature and concepts. Within this frame, aspects of major interest are the relationship between tradition and innovation, the status of genre, the proportion of autonomous and heteronomous creational dispositions within the artefacts or genres they belong to, as well as strategies of functionalization in the context of a given part of the cultural net. Contributions cover a broad range of topics, including poetics of Early Modern Drama; political, institutional and social practices; history of themes and motifs (Stoffgeschichte); history of genres/cross-fertilization between genres; textual traditions and distribution of texts; questions of originality and authorship; theories of circulation and net structures in Drama Studies.